Seminal and vagino-uterine microbiome and their individual and interactive effects on cattle fertility - Luecke, Sarah M.; Webb, Emily M.; Dahlen, Carl R.; Reynolds, Lawrence P.; Amat, Samat (Frontiers in Microbiology, 2022)
Reproductive failure is a major economical drain on cow-calf operations across the globe. It can occur in both males and females and stem from prenatal and postnatal influences. Therefore, the cattle industry has been making efforts to improve fertility and the pregnancy rate in cattle herds, as an attempt to maintain sustainability and profitability of cattle production. Despite the advancements made in genetic selection, nutrition, and the implementation of various reproductive technologies, fertility rates have not significantly improved in the past 50 years. This signifies a missing factor or factors in current reproductive management practices that influence successful fertilization and pregnancy. Emerging lines of evidence derived from human and other animals including cattle suggest that the microbial continuum along the male and female reproductive tracts are associated with male and female fertility – that is, fertilization, implantation, and pregnancy success – highlighting the potential for harnessing the male and female reproductive microbiome to improve fertility in cattle. The objective of this narrative review is to provide an overview of the recent studies on the bovine seminal and vagino-uterine microbiome and discuss individual and interactive roles of these microbial communities in defining cattle fertility.